2010
DOI: 10.1063/1.3488882
|View full text |Cite
|
Sign up to set email alerts
|

Active-oxidation of Si as the source of vapor-phase reactants in the growth of SiOx nanowires on Si

Abstract: Gold-coated silicon wafers were annealed at temperatures in the range from 800-1100°C in a N 2 ambient containing a low ͑3-10 ppm͒ residual O 2 concentration. A dense network of amorphous silica nanowires was only observed on samples annealed at temperatures above 1000°C and was correlated with the development of faceted etch-pits in the Si surface. Comparison with known thermodynamic data for the oxidation of Si and vapor-pressures of reactants shows that nanowire growth is mediated by a vapor-liquid-solid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Layers B and C correspond well to the positions of the original a‐Si and SiO 2 layers, respectively. In contrast to when the Si wafer acts as a Si source for the formation of NWs, as shown in the figure, both the Si wafer and layer C (SiO 2 coating) exhibited smooth surfaces, and layer C maintained its initial thickness. This demonstrates that neither the wafer nor the SiO 2 layer was involved in NW formation.…”
Section: Resultsmentioning
confidence: 89%
“…Layers B and C correspond well to the positions of the original a‐Si and SiO 2 layers, respectively. In contrast to when the Si wafer acts as a Si source for the formation of NWs, as shown in the figure, both the Si wafer and layer C (SiO 2 coating) exhibited smooth surfaces, and layer C maintained its initial thickness. This demonstrates that neither the wafer nor the SiO 2 layer was involved in NW formation.…”
Section: Resultsmentioning
confidence: 89%
“…Prolonged annealing results in lateral growth as SiO vapor is adsorbed onto the already grown nanowires, and NW samples with average diameters from 40 to 400 nm were readily obtained for shorter and longer anneal times, respectively. Further details of the nanowire growth process can be found elsewhere [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that it is possible to grow amorphous silica (SiO x ) NWs by a simple method involving the active oxidation of a Si substrate in the presence of metal catalyst particles, see for example references [10,11] and references within. This method eliminates the need for a gaseous precursor and can be used to grow dense networks of SiO x NWs.…”
mentioning
confidence: 99%
“…This vapor provides a gas-phase source for the VLS growth of silica NWs and in the presence of catalytic Au particles can be used to produce a dense network of SiO x NWs [14][15][16], typically tens of microns in thickness, as shown in Fig. 1(a).…”
mentioning
confidence: 99%
“…However, most investigations have focused on the effects of critical parameters such as the annealing temperature [21], metal catalysts [22], and O 2 concentration of the annealing gas [12][13][14][15], with very few reports about the role of the flow rate of the purging gas [23]. In this study, we have undertaken a comprehensive investigation of SiO x NW growth under active oxidation conditions, including the effects of O 2 partial pressure, temperature, and the flow rate of the annealing gas.…”
mentioning
confidence: 99%